FORAGE QUALITY OF MAIZE AND LEGUMES AS MONOCULTURES AND MIXTURES AT DIFFERENT SEED RATIOS - M. Ibrahim; M. Ayub; A. Tanveer; M. Yaseen (Journal of Animal and Plant Sciences, 2012)
Livestock is an important sector of agriculture, but good quality forage is one of the major limiting factors for the growth of this industry. Studies were conducted to compare the forage quality of maize and legumes sown in pure stand and in mixture in randomized complete blocks during 2005 and 2006 at the University of Agriculture Faisalabad, Pakistan. Maize (Zea mays L.) and three legumes [cluster bean (Cyamopsis tetragonoloba), cowpea (Vigna unguiculata (L.) Walp.), and sesbania (Sesbania sesban)] were sown at 100% the recommended seeding rate and in maize:legume mixtures at seed ratios (SR) of 75:25, 50:50 and 25:75. Crude protein (CP) and ether extractable fat (EEF) percentage of maize increased with the increase in seeding rate of legumes in all maize-legume mixtures over sole maize. Crude fibre (CF) percentage of forage maize was the maximum in sole maize. All monoculture legumes produced highest CP and EEF percentage than their mixtures with maize. Mixtures of maize-sesbania gave higher CP and EEF than maize-cowpea or maize-cluster bean at similar seed ratios, while cowpea sown alone or in mixture with maize had higher total ash than other legumes at same seed ratios. Farmers may grow maize+sesbania to get good quality forage.
Keywords: Forage quality; maize; cowpea; cluster bean; sesbania; seed ratio